Pembaharuan Pendidikan di Pondok Tahfidz dan Pesantren Modern (PTPM) Al-Huda Cawan - Thoriq, Jamal; Anshory, Muhammad Isa (TSAQOFAH, 2024)
Educational renewal is a necessity. This research aims to examine in more depth the educational reform at Pondok Tahfidz and Modern Islamic Boarding School (PTPM) Al-Huda Cawan. This research was conducted because of changing times and educational reforms in Islamic boarding schools, in the form of curriculum, methods, evaluation systems and management. The method used in this research is descriptive qualitative with a field research model. From the results of data observations, interviews and documentation, the results showed that educational reform at PTPM Al-Huda includes management, curriculum, entrepreneurship, moral learning, language skills training with native speakers and a strong synergistic relationship between the Islamic boarding school and the community to support the existence of the boarding school.